The Effect of Critical Thinking on Social Media Use, Tolerance, and Self-Assessment of Adolescents in Tulungagung, Indonesia - Zaenul Fitri, Agus (Technium Social Sciences Journal, 2021)
This study aims to examine and measure the influence of the effect of critical thinking on the use of social media, tolerance, and self-assessment of adolescents at school. Critical thinking has become a necessity for everyone in the era of the digitalization of technology. In dealing with the problems of adolescent life, critical thinking is one of the bases for taking action. Everyday teenagers are faced with very complex problems, such as addiction to the use of social media, lack of tolerance, and inaccurate self-assessment. Lack of literature that discusses the importance of critical thinking in dealing with these problems, researchers are interested in examining the effect of critical thinking on the use of social media, tolerance, and self-assessment of adolescents. This research was a quantitative method, by taking 206 adolescents aged 17-18 years as the research sample. The Statistical Package for the Social Sciences (SPSS) 25 software was used to conduct a one-way Multivariate Analysis of Variance (MANOVA) to determine the difference in effect on the dependent variable showing that there is an effect of critical thinking on the use of social media, tolerance, and self-assessment of adolescents. A percentage of the influence of critical thinking on self-assessment is higher than the use of social media or tolerance. Critical thinking and self-assessment have a very close relationship, so they have a higher influence. It turns out that critical thinking has a major influence on adolescent self-assessment, which is followed by the use of social media and a tolerant attitude. This research is expected to reinforce the importance of critical thinking in adolescents at schools.